PENERAPAN BERMAIN â€œTEMBAK IKANâ€ UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR MELEMPAR PADA SISWA KELAS IV SEMESTER II SD NEGERI KUTOWINANGUN 01 KEC. TINGKIR KOTA SALATIGA TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the increase in learning outcomes approach to playing the throw through fourth grade elementary school students Kutowinangun 01 Salatiga school year 2012/2013. Classroom Action Research is a qualitative study, data analysis techniques, using observation and assessment instruments also psychomotor, affective and cognitive. Based on the results that could, in cycle 1, the average value of the cognitive value of the average student 26 of 30, for the affective, the average student is a perfect 20 of 20, and for the value of psychomotor, reaching 37 of the maximum 50 points, while accumulative average value for this cycle is 83 out of a maximum 100, and completeness KKM reached 72.5%. In cycle 2 there is an increase in the cognitive and psychomotor aspects. For the cognitive aspect, the average rose 1 point to 27. For the affective aspect, because it has a maximum value in cycle 1, then there is an increase, and survive on an average value of 20. For psychomotor value, the average value also rose 3 points to 40. Of these three aspects, an increase in the average value of accumulative total of 4 points, which is 87, and completeness KKM also increased from 72.5% to 92.5%. Based on the above results, it can be concluded that the shooting game and fish can increase the ability of student learning outcomes in basic throwing motion at the fourth grade students of SDN 01 Kutowinangun Salatiga.